2018
DOI: 10.1097/md.0000000000013832
|View full text |Cite
|
Sign up to set email alerts
|

CDC20 overexpression leads to poor prognosis in solid tumors

Abstract: Background:A plenty of previous researches have reported the prognostic value of CDC20 (Cell Division Cycle Protein 20) in solid tumors. Nevertheless, these researches were restricted by the small sample databases and the results were not strongly consistent among them.Methods:We comprehensively searched these relevant studies by PubMed, Web of Science, and EMBASE, in which publications before March 2017 were included. Pooled HR values for OS were cumulatively pooled and quantitatively analyzed in the meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…CDC20 is a cell cycle regulating protein. A large number of studies have confirmed that CDC20 is upregulated in solid tumors and promotes cell growth and invasion leading to poor prognosis (Ding et al, 2017; Wang S. et al, 2018). Meanwhile, higher expression of CDC20 was found to be related to a high tumor grade and stage in common malignant tumors including EC (Gayyed et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…CDC20 is a cell cycle regulating protein. A large number of studies have confirmed that CDC20 is upregulated in solid tumors and promotes cell growth and invasion leading to poor prognosis (Ding et al, 2017; Wang S. et al, 2018). Meanwhile, higher expression of CDC20 was found to be related to a high tumor grade and stage in common malignant tumors including EC (Gayyed et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, targeting CDC20 in cancer may be a potential treatment strategy [31]. Wang et al reported that CDC20 serves as a meaningful prognostic biomarker in most cases of human solid tumours and that its high expression reduces patient survival [32]. HMGA-induced CCNB2 (a molecule of the cyclin clan) plays an important role in the development of mouse or human pituitary tumours [33].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that CDC20 is significantly overexpressed in different cancer types [ 8 ]. In order to better understand the role of CDC20 in cancer, we obtained RNA-Seq-based CDC20 expression levels in 33 human cancers from The Cancer Genome Atlas (TCGA) rich dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence indicates that CDC20 plays an important role in the development of human tumors [ 7 ]. CDC20 is overexpressed in a variety of human tumors including colorectal cancer (CRC) [ 8 , 9 ]. For example, CDC20 is overexpressed in both CRC cell lines and primary cancer tissues compared to normal colorectal epithelial cells and paracancerous tissue samples.…”
Section: Introductionmentioning
confidence: 99%